Understanding the role of instructor gestures during virtual lectures - Kelly, Stephanie; Kim, Jihyun; Chaudhary, Pankaj (Frontiers in Computer Science, 2025)
The purpose of this study was to establish the importance of instructor gestures in online lectures. Social information processing theory explains that virtual communication can be just as effective as face-to-face communication if communicators understand how to adapt their communication to the virtual channel. This study seeks to better understand the roles of camera distance and gestures in adapting lectures to virtual classrooms. An experiment examined the impact of student gender, camera distance from the instructor, and gesture use on instructor credibility, as measured by caring, competence, and trustworthiness. The results indicate that while camera distance did not impact students’ perceptions of instructor competence, the absence of gestures did impact how trustworthy and caring male students perceived the instructor to be. In the absence of gestures, male students perceived the instructor to be less caring and trustworthy. This indicates that instructors should make efforts to speak with gestures in virtual lectures, especially for male students, just as they do in the traditional classroom.